Quantitative Label-Free Proteomic Analysis of Milk Fat Globule Membrane in Donkey and Human Milk - Zhang, Xinhao; Jiang, Bo; Ji, Chuanliang; Li, Haijing; Yang, Li; Jiang, Guimiao; Wang, Yantao; Liu, Guangyuan; Liu, Guiqin; Min, Lingjiang; Zhao, Fuwei (Frontiers in Nutrition, 2021)
Donkey milk (DM), similar to human milk (HM) in compositions, has been suggested as the best potential hypoallergenic replacement diet for babies suffering from cow milk (CM) protein allergens. Milk fat globule membrane (MFGM) proteins are involved in many biological functions and important indicators of the nutritional quality of milk. In this study, label-free mass spectrometry analysis was conducted to quantitatively identify the differentially expressed MFGM proteins (DEPs) in DM vs HM group. In total, 293 DEPs were found in these two groups. DEPs were then subjected to intensive bioinformatic analysis. Results revealed that the majority of DEPs participated in regulation of immune system process, membrane invagination and lymphocyte activation. Kyoto Encyclopedia of Gene and Genomes (KEGG) pathways analysis found that these DEPs mainly participated in lysosome, galactose metabolism and PPAR signaling pathway. These results may provide valuable information in the composition of MFGM proteins in DM and HM, and expand our knowledge of different biological functions between DM and HM.